Contributions of the Linguistic Documentation to the Strengthening of the Ikpeng Language at School - Angela Chagas; Korotowï Taffarel; Maiua Txicão (Cadernos de Linguística, 2024)
In this paper, we present the activities and products developed during the Ikpeng language documentation project that contributed to the strengthening of the teaching of mother language of this indigenous society at the school, a space in which the use and teaching of the Portuguese language predominates. The Ikpeng linguistic documentation process was set within the Projeto de Documentação de Línguas Indígenas (PRODOCLIN), promoted by Museu do Índio/FUNAI, in partnership with UNESCO, during the period from 2009 to 2012. Among the main contributions of the documentation project are a sociolinguistic diagnosis, the creation of a lexical database, the elaboration of a descriptive grammar of the Ikpeng language, the publication of a monolingual book of traditional narratives and training courses in linguistics for indigenous teachers. The products resulting from the documentation were developed based on the demands of the school context of the Ikpeng society, to preserve and value the language and ancestral memories of this indigenous society. The Ikpeng language is spoken by the homonymous people, who live in the Parque Indígena do Xingu – MT.